Ontology and gnoseology of legal reality: current state of a problem in Ukraine - Бернюков, Анатолій Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
In this article the current state of research such legal category as «legal reality» is exposed to the analysis. Achievements and miscalculations of domestic science are critically comprehended. Thus the conclusion becomes that this concept should be considered in the light of development of philosophical and theoretical thought from a position legal ontology and gnoseology.